Influence of the coefficient of non-uniform expansion of the soil sample on mechanical characteristics - A. Z. Ter-Martirosyan; G. O. Anzhelo; L. Yu. Ermoshina; I. A. Bokov; A. V. Manukyan (Vestnik MGSU)
Introduction. The most common method of determining the mechanical characteristics of the soil is triaxial compression testing. This type of testing is widely used both for applied and scientific purposes, and is described in the works of both domestic and foreign authors, as well as in regulatory and technical documentation. However, within the framework of scientific works by various authors, the coefficient of uneven expansion of a soil sample during triaxial tests is often neglected and is not taken into account when processing the test results. In the existing current regulatory and technical documents, such as GOST 12248.3–2020, consideration of the coefficient of uneven expansion of the soil sample under triaxial compression b is of a recommendatory nature.Materials and methods. Within the framework of the work, experimental studies by the triaxial compression method were carried out on sandy soil samples of different granulometric composition in order to determine its mechanical characteristics using two different methods of processing laboratory test results — taking into account the coefficient of uneven expansion of the soil sample and without it.Results. According to the results of the performed experimental studies, it was found that the exclusion of the expansion non-linearity coefficient b from the processing of laboratory test results leads to a significant overestimation of the values of the internal friction angle. However, the values of secant modulus of deformation at 50 % strength E50 are lower by an average of 7.7 % when the nonlinear expansion coefficient of the steel is excluded from the processing.Conclusions. Analyzing the results obtained, as well as taking into account various factors influencing the results of the study (density, humidity, etc.), additional laboratory tests are required in order to further clarify the correlation dependencies in determining the strength and deformation characteristics of sandy soils, with and without taking into account the coefficient b.